Comparison of narcissism levels of students in the faculty of sports sciences in terms of some demographic variables - Menderes Kabadayı; Hasan Samet Abacı; Mehmet Yalcin Tasmekteplıgıl; Ali Kerim Yılmaz; Gul Cavusoglu (Selcuk University, 2017)
The purpose of this study is to find out the narcissism levels of the students in Faculty of Sports Sciences and to compare these in terms of some demographic variables. The sample of the study consists of a total of 180 students (66 females, 114 males) studying in three different departments of faculty of sports sciences (Physical Training and Sports Education, Sports Management and Coaching Education) who agreed to participate in the study voluntarily. In the study, Narcissistic Personality Inventory was used as data collection tool. The normality assumption tests of the data were conducted with Kolmogorov-Smirnov Test. Since the data did not meet the parametric test assumptions, nonparametric tests "'Mann-Whitney U" and "Kruskal Wallis" were used in order to find out the differences between personality traits and narcissism. Significant differences were found between age and the sub dimensions of exhibitionism and entitlement, between year of study and entitlement, and between being elite and exhibitionism and exploitativeness (p lt;0.05). In addition, branches and all sub dimensions were compared and no significant difference was found in any of the sub-dimensions (p gt;0.05). No significant difference was also found between total narcissism scores and the variables. As a conclusion, statistically significant difference was found between students' narcissistic personality traits and the variables of age, year of study and being elite. Based on these results, the fact that the students show narcissistic personality traits although they are still students shows that it is necessary to take the necessary steps before these attitudes and perceptions reach harmful extents and continue increasingly in their occupations.